Alcohol dehydrogenase 3 genotype as a risk factor for upper aerodigestive tract cancers - Nishimoto, I. N.; Pinheiro, N. A.; Rogatto, Silvia Regina [UNESP]; Carvalho, A. L.; de Moura, R. P.; Caballero, O. L.; Simpson, A.; Kowalski, L. P. (Amer Medical Assoc, 2004)
Objective: To assess alcohol dehydrogenase 3 (ADH3) polymorphism at position Ile349Val as indicator of risk factor for upper aerodigestive tract (UADT) cancer to verify its association with UADT cancer in nonalcoholic or nonsmoking individuals.Design: Cross-sectional study.Setting: Primary care or referral center.Patients: the study group consisted of 141 consecutive patients with newly diagnosed squamous cell carcinoma of the oral cavity, oropharynx, hypopharynx, or larynx admitted for surgical treatment. The comparison group consisted of 94 inpatients without cancer from the A. C. Camargo or other São Paulo (Brazil) hospital and 40 healthy individuals.Intervention: All participants were interviewed and data were collected using a structured questionnaire. After written informed consent was obtained, 20 mL of blood was collected in heparinized tubes.Main Outcome Measures: Odds ratio for ADH3 genotypes using logistic regression models.Results: After adjustment for sex, age, tobacco use, and history of cancer in first-degree family relatives, a significantly higher odds ratio for UADT cancer was observed among individuals with AA genotype and low cumulative alcohol consumption (:5 100 kg of ethanol) (odds ratio=3.8 [95% confidence interval, 1.5-9.7]). A 4-fold increase in odds ratio for UADT cancer among individuals with AA genotype and low tobacco consumption (:525 pack-years) was also found in the adjusted model.Conclusions: These results suggest that genotype AA may be a risk factor for UADT cancer, especially in individuals with low alcohol or tobacco consumption. However, further epidemiological case-control or cohort studies, preferably prospective, are needed to establish the exact role of ADH3 polymorphism and its association with the development of UADT cancers.